Noninvasive Evaluation of Portal Hypertension: Emerging Tools and Techniques - V. K. Snowdon; N. Guha; J. A. Fallowfield (International Journal of Hepatology)
Portal hypertension is the main cause of complications in patients with cirrhosis. However, evaluating the development and progression of portal hypertension represents a challenge for clinicians. There has been considerable focus on the potential role of noninvasive markers of portal hypertension that could be used to stratify patients with respect to the stage of portal hypertension and to monitor disease progression or treatment response in a longitudinal manner without having to undertake repeated invasive assessment. The pathogenesis of portal hypertension is increasingly understood and emerging knowledge of the vascular processes that underpin portal hypertension has paved the way for exploring novel biomarkers of vascular injury, angiogenesis, and endothelial dysfunction. In this paper we focus on the pathogenesis of portal hypertension and potential non-invasive biomarkers with particular emphasis on serum analytes.